HUBUNGAN ANTARA PRESTASI PRAKTIK KERJA INDUSTRI DAN PRESTASI KEWIRAUSAHAAN DENGAN MINAT BERWIRAUSAHA SISWA KELAS XII TEKNIK KENDARAAN RINGAN SMK NEGERI 5 SURAKARTA - Pramono, Dwi (Jurnal Nosel, 2012)
The purpose of research are (1) To know the state achievement industrial work practicum, achievement entrepreneurship, and interest entrepreneurial of class XII Teknik Kendaraan Ringan at SMK 5 Surakarta, (2) To know relation achievement industrial work practicum by interest entrepreneurial of class XII Teknik Kendaraan Ringan at SMK 5 Surakarta, (3) To know relation achievement entrepreneurship by interest entrepreneurial of class XII Teknik Kendaraan Ringan at SMK 5 Surakarta, (4) To know relation achievement industrial work practicum and entrepreneurship together by interest entrepreneurial of class XII Teknik Kendaraan Ringan at SMK 5 Surakarta. The research found that: (1) The student of class XII Teknik Kendaraan Ringan at SMK Negeri 5 Surakarta having an average value industrial work practicum and entrepreneurship are good as well as being entrepreneurial interest; (2) There is a positive relationship between achievement industrial work practicum students with interest entrepreneurial of class XII Teknik Kendaraan Ringan at SMK Negeri 5 Surakarta; (3) There is a positive relationship between achievement entrepreneurship with interest entrepreneurial of class XII Teknik Kendaraan Ringan at SMK Negeri 5 Surakarta; (4) There is a positive relationship between achievement industrial work practicum and entrepreneurship with interest entrepreneurial of class XII Teknik Kendaraan Ringan at SMK Negeri 5 Surakarta.